2004
DOI: 10.1074/jbc.m403538200
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of T Cell Receptor Signaling by Siglec-7 (p70/AIRM) and Siglec-9

Abstract: Siglec-7 (p70/AIRM) and Siglec-9 are "CD33"-related siglecs expressed on natural killer (NK) cells and subsets of peripheral T cells. Like other inhibitory NK cell receptors, they contain immunoglobulin receptor family tyrosine-based inhibitory motifs in their cytoplasmic domains, and Siglec-7 has been demonstrated to negatively regulate NK cell activation. Based on reports of the presence of these siglecs on T cells, we sought to determine if they are capable of modulating T cell receptor (TCR) signaling usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
164
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(178 citation statements)
references
References 51 publications
12
164
2
Order By: Relevance
“…Thus, weak constitutive interactions between clustered Siglec-5 and SHP-1 and/or SHP-2 could be important in maintaining leukocytes in the quiescent state until activation is triggered via appropriate receptors. Siglec-5 clustering and inhibitory signaling could be mediated via cis interactions with appropriately sialylated activatory receptors, as shown recently for Siglecs-7 and -9 in transfected human Jurkat T cells (36) and CD33 expressed on human monocytes (37).…”
Section: Discussionsupporting
confidence: 52%
“…Thus, weak constitutive interactions between clustered Siglec-5 and SHP-1 and/or SHP-2 could be important in maintaining leukocytes in the quiescent state until activation is triggered via appropriate receptors. Siglec-5 clustering and inhibitory signaling could be mediated via cis interactions with appropriately sialylated activatory receptors, as shown recently for Siglecs-7 and -9 in transfected human Jurkat T cells (36) and CD33 expressed on human monocytes (37).…”
Section: Discussionsupporting
confidence: 52%
“…Siglec-7 is an inhibitory receptor expressed on NK cells and to a lesser extent, monocytes and a subset of CD8ϩ T cells (13,(17)(18)(19)(20)(21). In vitro binding studies have revealed that Siglec-7 shows a marked preference for glycoconjugates bearing ␣(2,8)-linked disialic acid and branched ␣(2,6)-linked sialic acid (22).…”
mentioning
confidence: 99%
“…Although Siglec-5 is expressed predominantly on myeloid cells such as neutrophils and monocytes/macrophages, Siglec-10 is also expressed on B cells (6,10), and recent evidence suggests that Siglec-10 acts with properly glycosylated CD52 to allow binding and inhibition of T cell activation (51). Moreover, Siglec-9 is expressed on a subpopulation of CD8 T cells (54). Therefore, up-regulation of LGALS3BP may directly influence T cell activation against tumors and hamper the generation of an antitumoral Th1 immune response.…”
Section: Discussionmentioning
confidence: 99%